A microstrip antenna with reduced in-band and out-of-band radar cross-section. Issue 2 (13th November 2018) - Zhang, Jiakai; Xu, Jiachen; Qu, Yan; Ding, Jun; Guo, Chenjiang
Abstract : This paper proposes a microstrip antenna with reduced in-band and out-of-band radar cross-section (RCS) by subtracting the area of weak scattered current on the ground plane. Fourteen square slots were subtracted from the ground plane, reducing in-band and out-of-band RCS while maintaining radiation performance. Modified and reference antenna surface current distributions were simulated and analyzed in radiating and scattering modes. Two antenna prototypes were fabricated and measured to verify the simulation. The proposed antenna RCS was reduced compared with the reference antenna in the frequency range 1–4.4 GHz, including in-band and out-of-band frequency bands. Maximum in-band and out-of-band RCS reduction was 16.3 dBsm at the working frequency, and 19.3 dBsm at 3.4 GHz, respectively